Polymer-metal salt composite for dehydration from desulfurized gas and liquid condensate streams
By using a composite material of water-soluble polymer and metal salt as adsorbent, the problem of high temperature and insufficient water adsorption capacity in the prior art is solved, and the water adsorption capacity is improved at a lower temperature and energy is reduced Consumption and operational costs.
Patent Information
- Application Number
- CN202380036927.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-28
- Filing Date
- 2023-04-28
- Publication Date
- 2024-12-13
AI Technical Summary
Prior Art In the process of removing water from desulfurization gas and liquid condensation streams, the regeneration of adsorbents requires high temperatures, resulting in increased energy consumption and low water adsorption capacity, resulting in a long regeneration cycle time.
A composite material including water-soluble polymer and metal salt is used as an adsorbent to form a metal/water-soluble polymer composite material by cross-linking, which is used to dry the hydrated hydrocarbon stream, reduce the regeneration temperature, and improve the water adsorption capacity.
It achieves improved water adsorption capacity at lower regeneration temperatures, reduces energy consumption, and extends regeneration cycle time, provides stable, renewable absorbents, and reduces operating costs.
Smart Images

Figure HDA0005105256050000011
Abstract
Description
Background Art
[0001] In many chemical processes, the removal of water is particularly important. Removing water from natural gas or hydrocarbon condensate streams is one such process. When oil or gas is produced from a well, there is usually water present from the reservoir and other sources that needs to be removed. This material needs to be dehydrated to prevent damage to downstream equipment. Dehydration can be performed after removing other contaminants (such as hydrogen sulfide). This is usually performed using an adsorbent. Summary of the invention
[0002] This summary is provided to introduce some concepts that are further described below in the detailed description. This summary is not intended to identify key or essential features of the claimed subject matter, nor is it intended to be used as an aid in limiting the scope of the claimed subject matter.
[0003] In one aspect, embodiments disclosed herein relate to compositions and methods for removing water from sweet gas and liquid condensate streams, and a method for preparing a metal / water-soluble polymer composite material. The composition includes a water-soluble polymer and a metal salt. The mass ratio of the metal salt to the water-soluble polymer is in the range of about 1:1 to about 5:1. The water-soluble polymer forms a cross-linked material with the metal salt. The composition can be used to dry a hydrated hydrocarbon stream, and a dehydrated hydrocarbon stream is prepared by passing the hydrated hydrocarbon stream through one or more temperature swing adsorption vessels containing the composition.
[0004] The method of preparing the metal / water-soluble polymer composite material may include mixing a water-soluble polymer that is not cross-linked with a metal salt and water to form a paste. The paste is dried.
[0005] Other aspects and advantages of the claimed subject matter will be apparent from the following description and the appended claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0006] The figure is a plot of the experimental results of the implementation schemes of Example 1, Example 2 and Comparative Example 1. DETAILED DESCRIPTION
[0007] The adsorbent used to remove water becomes saturated and must be regenerated before it can be reused. This regeneration typically requires high temperatures, which requires heating, usually using hot regeneration gases. These hot regeneration gases must be heated themselves, which requires additional energy. Lowering the temperature of these gases can reduce the energy required to produce them. In addition, increasing the water adsorption capacity is also useful because the time between regeneration cycles can be longer than if the water adsorption capacity was reduced.
[0008] In one or more embodiments, a lower regeneration temperature of the adsorbent can be achieved by using a composite material comprising a water-soluble polymer and a metal salt. In one or more embodiments, such a composite material can have an increased water adsorption capacity compared to many molecular sieve desiccants adsorbents. The inventors have found that embodiments can be produced via a limited number of steps using materials that are typically relatively inexpensive compared to many materials known to those skilled in the art.
[0009] Water-soluble polymers are polymers that are able to dissolve in water. These polymers, when dissolved in water, increase the viscosity of the resulting solution. Furthermore, solutions of water-soluble polymers and water often exhibit non-linear rheology. Pure water-soluble polymers, when not in a composite material, will dissolve upon addition of water and are therefore not suitable for use as desiccants.
[0010] In one or more embodiments, the water-soluble polymer may be cross-linked by adding a metal salt. In one or more embodiments, the water-soluble polymer is not cross-linked prior to mixing with the metal salt. This is because, in some cases, the cross-linked polymer may simply swell in water to form a gel and may not form a paste when combined with the metal salt. In one or more embodiments, the water-soluble polymer may be ground into a powder form prior to introduction into the metal salt.
[0011] In one or more embodiments, the water-soluble polymer may include, but is not limited to, homopolymers, copolymers, blends, and combinations thereof. In one or more embodiments, the water-soluble polymer may include, but is not limited to, one or more of polyvinyl alcohol, polyethylene glycol, gum arabic, guar gum, or any combination thereof. In one or more embodiments, the water-soluble polymer may include, consist of, or consist essentially of guar gum.
[0012] Metal salts include compounds that form metal hydrate salts after adding water. Typically, metal hydrate salts allow absorption of water and include metals, ions, and water molecules combined in a certain proportion. For example, copper sulfate pentahydrate includes five water molecules combined with a copper sulfate salt. Metal hydrate salts can be dehydrated, whereby water is removed, leaving only metals and ions. One method of achieving this purpose is by heating. In one or more embodiments, the metal salt may include, but is not limited to, copper sulfate, aluminum nitrate, calcium chloride, magnesium sulfate, nickel nitrate, and magnesium chloride. In other embodiments, the metal salt may include copper sulfate or aluminum nitrate, be composed of copper sulfate or aluminum nitrate, or be substantially composed of copper sulfate or aluminum nitrate.
[0013] According to the embodiments of the present invention, the process of forming a metal / water-soluble polymer composite material involves contacting a water-soluble polymer with a metal salt, forming a paste and drying. The water-soluble polymer, the metal salt or both can be in the form of a powder before mixing. The mixing of the metal salt, the water-soluble polymer and water can be carried out in any order, such as mixing the metal salt and the water-soluble polymer, then adding water, or for example, mixing water and the metal salt, and then adding the dissolved salt mixture to the water-soluble polymer. In some embodiments, after forming a paste, the resulting composition can be formed into pellets, tablets or other shapes, such as by extrusion, tabletting or other processes known to those skilled in the art and drying.
[0014] In one or more embodiments, the resulting paste and the resulting absorbent composition may have a mass ratio of metal salt to water-soluble polymer (both on a dry basis) in the range of about 1: 1 to about 5: 1. The ratio of the weight of the metal salt to the weight of the water-soluble polymer may have an upper limit of about 5: 1, 4: 1, 3: 1, or about 2.5: 1, and a lower limit of about 1: 1, 1.5: 1, 1.75: 1, or about 1.9: 1, wherein any upper limit may be combined with any lower limit.
[0015] As described above, sufficient water can be added to form a paste, which can then be dried. In one or more embodiments, the mass ratio of water to the water-soluble polymer in the paste can be in the range of about 3:1 to about 10:1. The ratio range of water to the water-soluble polymer can have an upper limit of about 10:1, 7:1 or about 5:1 and a lower limit of about 3:1, 3.3:1 or about 3.5:1, wherein any upper limit can be combined with any lower limit. Insufficient water may cause the metal salt to be unable to fully mix and associate with the water-soluble polymer and form a paste. On the other hand, too much water may also cause the quality of the mixture to be insufficient, such as being unable to form a paste that is easy to extrude, shape and dry.
[0016] In other embodiments, the polymer can be dissolved in water before mixing with the metal salt. In other embodiments, the polymer and the metal salt can also be ground into powder together and then mixed with water. Both the polymer and the metal salt can be in powder form before mixing with water in any order. In one or more embodiments, one or more components can be mixed using any method apparent to those skilled in the art, such as, for example, in a kneader or continuous mixer. The resulting mixture may be uniform before further processing. The paste can then be formed into aggregates (conglomeration, or agglomerates) by any method apparent to those skilled in the art, such as by extrusion or tabletting.
[0017] The drying of the paste or extrudate can be carried out in air at ambient conditions, under vacuum, at elevated temperatures, or a combination of these conditions. For example, in some embodiments, air can be used to dry the paste or extrudate at ambient conditions. In other embodiments, the paste or extrudate can be dried under vacuum at elevated temperatures. In other embodiments, the paste or extrudate can be partially dried using ambient air and then dried under vacuum at elevated temperatures.
[0018] In some embodiments, the paste or extrudate may be exposed to air for at least 24 hours (h) of drying. In other embodiments, the paste may be exposed to air for 24h to 120h of drying. In other embodiments, the paste may be exposed to air for 48 to 96 hours of drying. Drying may also occur in air, nitrogen at high temperatures or under vacuum in a shorter time, such as in air at a temperature of 110°C (230°F) or under vacuum at 60°C (140°F) for 8h to 96h, such as about 16 hours.
[0019] In one or more embodiments, the paste or extrudate, or the partially dried paste or extrudate obtained by air drying, can be dried under vacuum and / or at high temperature. In one or more embodiments, after the previous air drying, the paste can be allowed to dry in vacuum for at least 12 hours. In other embodiments, after air drying, the paste can be allowed to dry in vacuum for about 18 hours to about 48 hours. In one or more embodiments, the vacuum can be in a pressure (absolute pressure) ranging from a maximum value of about 0.2 bar or about 0.1 bar to a minimum value of about 0.001 bar or about 0.01 bar, wherein any maximum value can be combined with any minimum value. In one or more embodiments, drying under vacuum can occur at a temperature of about 50°C to about 110°C. In other embodiments, drying under vacuum can occur at a temperature in the range of about 60°C to about 100°C. In some other embodiments, drying under vacuum can occur at a temperature in the range of about 65°C to about 85°C.
[0020] In one or more embodiments, the resulting material is cross-linked. Cross-linking may occur between the oxygen atoms in the guar gum and the metal ions, and the metal acts as a bridge. The composite material may be homogeneous. The composite material can have any desired geometric shape, which can include, but is not limited to, rods, balls, particles, pellets or combinations thereof. The resulting product can have a water adsorption capacity in the range of 10 mol / g to 30 mol / g.
[0021] In one or more embodiments, the composite material can be used to remove water from a water-containing hydrocarbon stream (such as a sweetened gas or condensate). In one or more embodiments, this can be achieved by temperature swing adsorption. In temperature swing adsorption, typically two or more temperature swing adsorption vessels have an adsorbent, wherein at least one vessel is in an adsorption mode and one or more vessels are in a regeneration mode. According to one or more embodiments, the container is filled with a composite material, which acts as an adsorbent. The hydrated hydrocarbon stream is sent through one or more temperature swing adsorption vessels to produce a dehydrated hydrocarbon stream. At any given time, at least one container is used to remove a component (in this case, water) from a gas or liquid stream. Since the composite material becomes saturated over time, at least one other container is being regenerated at any given time. That is, the hot regeneration gas is sent through one or more regenerated temperature swing adsorption vessels to remove the component (in this case, water) from the composite material. This allows continuous operation to be achieved by switching between containers.
[0022] The hot gas used in temperature swing adsorption needs to be heated, so any reduction in the temperature required for regeneration can reduce the energy consumed by heating the gas. The regeneration of the metal salt / water-soluble polymer composite material according to the embodiments of the present invention can, for example, be carried out using air or nitrogen as the desulfurization gas. Regeneration can also be carried out at a relatively low temperature, similar to the temperature used for drying the paste, such as in the range of about 100°C to 130°C. In contrast, the drying of molecular sieves typically requires a temperature of more than 250°C. Here, the desulfurization gas can be defined as natural gas that does not contain a large amount of H2S. Specifically, the desulfurization gas does not contain more than 10ppmv of H2S. Condensate is defined as liquid hydrocarbons, such as those that may be condensed from natural gas during the treatment of hydrocarbons (e.g., ethane, propane, butane) from the wellbore. In some embodiments, the condensate may have the same H2S specifications as the desulfurization gas before being sent to the dehydrator.
[0023] Example 1
[0024] Preparation of composite materials
[0025] 1 g of guar gum and 3.5 g of copper (II) sulfate pentahydrate were mixed in a mortar and pestle until a homogeneous mixture was produced. Water was added dropwise until a homogeneous paste was produced. The material was transferred to a needle-free syringe, from which an extrudate was produced. The extrudate was dried in air for three days and then dried at 70° C. under vacuum for 24 hours. The extrudate was then cut into lengths.
[0026] Example 2
[0027] 3.5 g of aluminum nitrate nonahydrate were dissolved in water. 1 g of guar gum was added and mixed until a homogeneous paste was obtained. The material was transferred to a needleless syringe, from which an extrudate was produced. The extrudate was dried in air for three days and then at 70° C. under vacuum for 24 hours. The extrudate was then cut into lengths.
[0028] Comparative Example 1
[0029] NBA-8 molecular sieve was used as a comparative example. NBA-8 is a 4A type 1 / 8 inch (2.5 to 5 mm) molecular sieve comprising crystalline aluminum silicate having a uniform three-dimensional structure composed of aluminum oxide and silicon dioxide tetrahedrons, and having a regeneration temperature of 550°F.
[0030] Experimental testing
[0031] use Production 3FLEX Autosorb was tested on example compositions and comparative molecular sieves at about 20°C and about 1 bar.
[0032] The results are shown in the figure.
[0033] The aluminum nitrate nonahydrate / guar gum composite material shown in Example 2 and the copper sulfate pentahydrate / guar gum composite material shown in Example 1 show improved water absorption when exposed to high humidity gas when compared with NBA-8 of Comparative Example 1. When compared with NBA-8, both the copper sulfate / guar gum composite material and the aluminum nitrate / guar gum composite material have improved adsorption capacity, and the copper sulfate / guar gum shows a greater improvement in adsorption. When used for dehydration, when compared with NBA-8, improving adsorption capacity through one or more embodiments can use less adsorbent, smaller containers, lower pressure drops, or all three. Further, the regeneration gas temperature of these materials is lower, such as 230°F, compared to the regeneration gas temperature of NBA-8 molecular sieve is 550°F. This allows reducing the heat load of the dehydrator and reducing operating costs (OPEX).
[0034] It has also been found that embodiments of the present invention using guar gum provide stable, regenerable composite materials. In other words, they can be used as absorbents and regenerated through multiple cycles without problems.
[0035] Although only a few exemplary embodiments have been described in detail above, those skilled in the art will readily appreciate that many modifications may be made to the exemplary embodiments without departing substantially from the present invention. Therefore, all such modifications are intended to be included within the scope of the present disclosure as defined by the appended claims.
Claims
1. A composition of material for removing water from a water-containing hydrocarbon stream, the composition include: Water-soluble polymers and metal salts; wherein the dry weight ratio of the metal salt to the water-soluble polymer is in the range of about 1:1 to about 5:1; and wherein the water-soluble polymer and the metal salt form a cross-linked material.
2. The composition of claim 1, wherein the water soluble polymer comprises guar gum.
3. The composition according to claim 1 or 2, wherein the metal salt is selected from the group consisting of copper sulfate and aluminum nitrate.
4. The composition according to any one of claims 1 to 3, wherein the dry weight ratio of the metal salt to the water-soluble polymer is from 1.5:1 to 4:
1.
5. A method for drying a hydrated hydrocarbon stream, include: The hydrated hydrocarbon stream is passed through one or more temperature swing adsorption vessels to produce a dehydrated hydrocarbon stream, wherein the one or more temperature swing adsorption vessels contain the composition of claim 1.
6. The method of claim 5, further comprising passing a regeneration gas through the one or more thermal swing adsorption vessels at a temperature in the range of about 100°C to about 130°C.
7. A method for preparing a metal / water-soluble polymer composite material, include: mixing a non-crosslinked water-soluble polymer with a metal salt and water to form a paste; as well as The paste is dried.
8. The method of claim 7, further comprising extruding the paste.
9. The method according to claim 7 or 8, further comprising cross-linking the metal with the non-cross-linked water-soluble polymer to form a metal / water-soluble polymer composite material.
10. The method according to any one of claims 7 to 9, wherein the metal salt is dissolved in the water prior to the mixing.
11. The method according to any one of claims 7 to 10, wherein the metal salt and the water-soluble polymer are mixed before adding the water.
12. The method according to any one of claims 7 to 11, wherein the drying comprises placing the paste under vacuum at a temperature of 50°C to 110°C.
13. The method of claim 12, wherein the paste is under vacuum for at least 12 hours.
14. The method of any one of claims 7 to 13, wherein the drying comprises exposing the paste to air for at least 24 hours.
15. The method of any one of claims 7 to 14, wherein the water soluble polymer comprises guar gum.
16. The method according to any one of claims 7 to 15, wherein the metal salt is selected from the group consisting of aluminum nitrate and copper sulfate.
